Factors influencing undergraduate attitudes and decision making regarding a career in production animal practice - Payne, Emily (2024)
The objective of the research discussed in this thesis was to determine what influences undergraduate veterinary students’ attitudes when considering farm animal practice as a future career discipline and how these factors are influenced by experiences gained during students’ time as an undergraduate at veterinary school. This research is of relevance during this time of change within the veterinary profession; with increasing numbers of students being offered the opportunity to study veterinary medicine but an undeniable recruitment and retention crisis within the wider profession.